COVID-19 Dialogue on Facebook: Crisis Communication Relationship between Ghanaian Authorities and Citizens (Journal of International Crisis and Risk Communication Research, 2022)
The paper explored how the Ministry of Information (M.O.I.), the official mouthpiece of the government of Ghana, interacted with citizens during the COVID-19 outbreak within the context of crisis communication as a tool for authority-citizen engagement on Facebook. Content analysis of COVID-19 comments on the Ministry of Information’s official Facebook page showed higher participation in the discussion from citizens. However, authorities only provided information by being inactive participants in the interaction. The dominant issues focused on Ghanaian authorities and their actions, the course of events surrounding the pandemic, infected cases and deaths, and Ghana’s recovery efforts. The active publics provided information, asked and answered questions, and expressed their opinions as the discussions were ongoing. The comments portrayed negative, positive, and neutral tones. The paper also revealed diverse challenges that are likely to hinder crisis communication during the pandemic, from the inflexibility of action, quality of information, and disparity of knowledge.